Analisis Penerimaan Pengguna Kartu Top-Up di Summarecon Mall Bekasi Menggunakan Technology Acceptance Model (TAM) - Rahman, Taufik; Chairudin, Muhammad Rio; Sumarna, Sumarna (Jurnal Ilmiah SINUS, 2025)
In the digital era, electronic payment systems are increasingly developing, including the use of top-up cards in shopping centers. However, the level of acceptance and effectiveness of top-up cards in increasing transaction efficiency is still a question. This study aims to analyze the factors that influence the acceptance of the top-up card payment system at Summarecon Mall Bekasi using the Technology Acceptance Model (TAM). The research method used is quantitative by distributing questionnaires to 80 respondents who are top-up card users. Data analysis was carried out through validity and reliability tests, multiple linear regression, and hypothesis testing to test the effect of Perceived Usefulness, Perceived Ease of Use, Attitude Toward Using, and Behavioral Intention on the acceptance of top-up cards. The results showed that Perceived Usefulness had the most significant effect on the acceptance of top-up cards, followed by Behavioral Intention, while Perceived Ease of Use and Attitude Toward Using also contributed but with a smaller effect. The regression model showed that 78% of the variation in top-up card acceptance could be explained by the variables in the TAM. The conclusion of this study confirms that increasing the use of top-up cards can be done by increasing the benefits felt by users, simplifying the top-up system, and increasing socialization and education to users. The results of this study provide insights for mall managers and payment service providers in increasing transaction efficiency and encouraging the adoption of digital payment systems in modern retail environments.